2017
DOI: 10.4077/cjp.2017.bag511
|View full text |Cite
|
Sign up to set email alerts
|

Pacing Profiles in Age Group Cross-Country Skiers in the Vasaloppet 2012-2016

Abstract: Little is known for pacing profiles in age groups cross-country skiers. The aim of the present study was to examine the effect of sex, age and calendar year on pacing strategies in the largest ski marathon in the world. All finishers (n = 66,435) in ‘Vasaloppet’ from 2012 to 2016 were examined for 12 different age groups (G). There was an association between age group and sex (χ² = 1091.1, P < 0.001; Cramer’s V = 0.13, P < 0.001), where the men-to-women ratio in each age group ranged from 3.29 (in G₂₀) to 64.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
1
15
1
Order By: Relevance
“…For instance, a greater change in speed was found among females than among males in the Engadin Ski Marathon 16 and in a previous study using fewer years (2012‐2016) in the Vasaloppet race. 5 In contrast to our present findings, it has been shown that females were better pacers (i.e., with more even pacing) than males in marathon running. 9 , 10 This disagreement indicates a likely variation in the effect of sex on pacing among different endurance sports.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For instance, a greater change in speed was found among females than among males in the Engadin Ski Marathon 16 and in a previous study using fewer years (2012‐2016) in the Vasaloppet race. 5 In contrast to our present findings, it has been shown that females were better pacers (i.e., with more even pacing) than males in marathon running. 9 , 10 This disagreement indicates a likely variation in the effect of sex on pacing among different endurance sports.…”
Section: Discussioncontrasting
confidence: 99%
“…Considering the effect of sex on pacing, a remarkable observation was that females presented greater changes in speed at the stations (i.e., percent change from the preceding to the following split) than males. This observation indicated that males show a more even pacing, which was in partial agreement with the existing literature concerning XC skiing 5 , 16 but not for other sports. For instance, a greater change in speed was found among females than among males in the Engadin Ski Marathon 16 and in a previous study using fewer years (2012‐2016) in the Vasaloppet race.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Then from this event, some students will be selected and sent to participate at the next level of cross-country race in Majlis Sukan Sekolah Daerah (MSSD). There are three categories; below 12 years old (4 kilometers), below 15 years old (6 kilometers) and below 18 years old (8 kilometers) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-country (XC) skiing is one of the most popular winter endurance sports, especially in countries in the central and north Europe. Considering the increased participation of master XC skiers in training and competition, an increased scientific interest has been focused on performance aspects such as age of peak performance and variation of sex difference by age [ 1 4 ]. The average age of women and men XC skiers in a very popular race, Engadin ski marathon, is 38 and 44 years old, respectively [ 3 ].…”
Section: Introductionmentioning
confidence: 99%